Novel phytochemical Cissus quadrangularis extract–loaded chitosan/Na-carboxymethyl cellulose–based scaffolds for bone regeneration. (November 2018) - Tamburaci, Sedef; Kimna, Ceren; Tihminlioglu, Funda
Medicinal plants are attracting considerable interest as a potential therapeutic agent for bone tissue regeneration. Cissus quadrangularis L. is also a medicinal plant known with its osteogenic activity. In this study, a phytochemical scaffold was produced by incorporating Cissus quadrangularis with chitosan/Na-carboxymethyl cellulose blend by lyophilization technique. The effect of Cissus quadrangularis loading on the mechanical, morphological, chemical, and degradation properties as well as in vitro cytotoxicity, cell proliferation, and differentiation of the composites was investigated. Scanning electron microscopy images showed that porous Cissus quadrangularis –loaded scaffolds were obtained with an average pore size of 148–209 µm which is appropriate for bone regeneration. Cissus quadrangularis incorporation enhanced the compression modulus of scaffolds from 76 to 654 kPa. In vitro cell culture results indicated that Cissus quadrangularis /chitosan/Na-carboxymethyl cellulose scaffolds provided a favorable substrate for the osteoblast adhesion, proliferation, and mineralization. Results supported the osteoinductive property of the Cissus quadrangularis extract–incorporated scaffolds even without osteogenic media supplement. Cissus quadrangularis extract increased the alkaline phosphatase activity of the SaOS-2 cells on scaffolds on 7th and 14th days of incubation. The investigation of characterization and cell culture studies suggest that Cissus quadrangularis –loaded osteoinductive Cissus quadrangularis /chitosan/Na-carboxymethyl cellulose scaffold can serve as a potential biomaterial for bone tissue engineering applications.